Peran Orang Tua Terhadap Pembelajaran Dalam Jaringan (daring) Pada Masa Pandemi Covid-19 - Lemi Susanti; Luthfi Hamdani Maula; Rahman Eri Pridana (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
This research is a qualitative descriptive study that aims to determine the role of parents during the learning process at home in an effort to break the chain of the spread of the Covid-19 virus. This research method uses a qualitative approach with descriptive methods. Data obtained using the interview method using google form consisting of 10 questions given to informants, namely parents of class V B students and who filled in only 17 informants. the role of parents is really needed in assisting children when learning online. The purpose of this study was to determine the role of parents in online learning during the Covid-19 Pandemic. The conclusion of this study is based on the results of interviews conducted with informants, most parents always accompany their children when the online learning process is done even though there are some parents who work and can not accompany, but communication with class teachers remains well established so that parents can still supervise online learning even though it is not yet fully. as well as their children are considered to be able to do learning at home very well. Parents also feel that through online learning, parents can see their children's development in learning.